ANALISIS PERATURAN PEMERINTAH NOMOR 26 TAHUN 2023 SEBAGAI BENTUK PERLINDUNGAN DAN PELESTARIAN EKOSISTEM LAUT - Simanjuntak, Patricia Bela (2024)
In order to optimize the government's policy as written in Law No. 32/2014 on Maritime Affairs, the Indonesian government established Government Regulation No. 26 of 2023 concerning Management of Marine Sedimentation Results. According to the Coordinating Ministry for Maritime Affairs and Investment, this regulation was established with the aim of solving the problem of sedimentation results in the sea and optimizing its use for the benefit of economic welfare and preservation of the marine environment. The author aims to analyze government policies in supporting the maintenance of the carrying capacity of coastal and marine ecosystems in order to achieve the protection and preservation of Indonesia's nature in context of Law Number 27 of 2007 concerning Management of Coastal Areas and Small Islands. There are several problems that cause this policy to be finally established, namely the urgency in handling the life of marine ecosystems related to coral reefs that are covered by sedimentation and deposition results that interfere with the shipping sector. The author will discuss how government regulation No. 26 of 2023 concerning Management of Marine Sedimentation Results can fulfill the urgency that is a concern caused by sedimentation results in the sea. In making this paper, the author uses normative legal research methods. Where in the normative legal research method focuses more on examining the rules, norms and rules in positive law that have a correlation with the problems to be studied. The establishment of a new policy cannot avoid controversy from dissatisfied parties. However, it needs to be realized that this policy is a form of government attention in improving the welfare of the community and preserving marine ecosystems in improving community welfare and preserving marine ecosystems in meeting the needs of the environment and coastal communities.